Development of forewarning system of potato aphid (Myzus persicae) on potato (Solanum tuberosum) in India - TRIVEDI, T P; PAUL KHURANA, S M; PURI, S N; BHAR, L M; MEHTA, S C; JAIN, R C; SINGH, G; CHAUDHARI, S M; MOHASIN, M; DHANDAPANI, A; CHONA, NAVEEN (The Indian Journal of Agricultural Sciences, 2014)
In the present study an attempt was made to develop forecasting models for predicting potato aphid [Myzus persicae (Sulzer)] population in India. The data for present study were collected at Pantnagar (Uttaranchal); Kalyani (West Bengal) and Deesa (Gujarat) during 1974-75 to 1996-97 under All-India Co-ordinated Potato Improvement Project. Different types of methods were tried for forecasting pllrpose. Non-linear models were found to be the best fitted. Validation for these models were carried out using data collected in 1995-96 and 1996-97 and applied during the season 2000-2001 at Kalyani and Deesa and compared with the actual population of aphids collected later.